READING IN ACTION THE EFFECT OF COLLABORATIVE STRATEGIES TOWARDS STUDENTS' LEARNING ACTIVITIES AND READING COMPREHENSION - Firman, Edi (IKIP Mataram, 2017)
Reading is still considered as a difficult skill to be taught and learnt, some students have difficulties in comprehending the text and reading also regarded as passive activities instead of active activity. This Research is aimed to know the effect of collaborative strategies towards students' learning activities and reading comprehension. This research is quasi-experimental pre-test post-test design. The data were analyzed using paired samples, independent test and correlation. The result proved that the experimental post-learning activities are higher than pre-activities (83.27 > 61.20) and ttest 16.434. The independent test also clarified that the experimental group performed greater learning activities t (5.322 > 2.000). In Reading, the experimental post-test mean score is higher than pre-test (59.44 > 47.41), and ttest (4.237 > 2.021). The independent samples test confirmed that the experimental group ttest is higher than ttable. (3.777 > 1.980). Meanwhile the correlation analysis proved that rtest is smaller than rtable (0.134 ?0.199) very low category. It can be concluded that collaborative strategies are effective towards students' learning activities and reading comprehension, although there is no correlation between learning activities and reading comprehension.